Development and validation of self-care requisites assessment - Moshtagh Eshgh, Zahra; Mirzaei, Soghra; pazargadi, Mehrnoosh; Alavi Majd, Hamid; Abed Saeedi, Zhila (Advances in Nursing & Midwifery, 2012)
Abstract Background: Assessment of patient’s needs is the first step for recognizing problems and prevention of complications. Assessment tools are needed in order assess needs, and plan nursing care to prevent complications such as diabetic foot ulcer .The purpose of the present study was to develop self-care requisites assessment tool for prevention of diabetic foot ulcer and examine its validity and reliability. Material and Methods : This methodological study consisted of two phases, phrase I was development of the comprehensive assessment form, for which a qualitative study and a literature review was conducted. Phase 2consisted of testing the instrument for validity and reliability. In qualitative study unstructured interviews were conducted with 8 patients with type 2 diabetes. Validity of the instrument was measured by content validity, concurrent validity (criterion related validity) and construct validity. A sample of153 type two diabetic patients were selected to conduct factor analysis of the tool. Reliability was confirmed by internal consistency. Data were analyzed by SPSS statistical software. Findings: The initial form consisted of 103 items. Final version of self –care requisites assessment form for preventing diabetic foot ulcer consisted of 43 items with 5 sub scales. Validity was established for content, construct and concurrent validity. Content validity was assured by a panel of experts .Concurrent validity was measured by comparing the scores from assessment tool with self-care agency and diabetic clients' quality of life scales, which demonstrated an acceptable correlation among the scores. Internal consistency reliability of the tool was demonstrated with Cronbach's P coefficient ranged from 0.70 to 0.89 for subscales, the overall test re test reliability was 0.97. . Conclusion The self-care requisite assessment tool for prevention of diabetic foot ulcer is a reliable and valid instrument to measure self-care needs for prevention of diabetic foot among individuals with type two diabetes mellitus. Key words : Orem model, Tool development, Diabetes, self-care requistis EFERENCES -Azizi F (2008). [Started learning course "foot care nurse" promise for prevention and care of diabetic foot]. Iranian Journal of Endocrinology and Metabolism. 4 (10) 297-298. (Persian). -Burns N, Grove SK (2006). Understanding Nursing Research Building an Evidence Based Practice. 4 th edition. St Louis, Mosby. -Darvishpoor Kakhaki A et al (1384). [Instrument development to measure diabetic client quality of life.] Iranian Journal of Endocrinology & Metabolism.7 (2) 149-155. (Persian) -Dehghan Nayyeri N, JalaliNia F (2005). [Theory Development and Nursing Theory]. Tehran, Boshra Pub. (Persian). -Evans s et al (2000). Selecting a mental health need assessment scale: Critical appraisal of standardized measure. Journal of Evaluation in Clinical Practice. 6(4)379-393. -HejaziSh (2007). [Introduction to the Principle and Methods in Medical Research]. Tehran: Islamic Azad University. Tehran, Medical Unit Pub. (Persian). -Holloway F (1994) Need in community psychiatry: A consensus is required. Psychiatric Bulletin.18 (6)321-323. -Moore JB (1995). Measuring the self-care Practice of children and adolescents: Instrument development. Maternal- Child Nursing Journal. 23(3) 101-108. -Moore JB et al (2005). Development and examination of self-care Instrument to measure nutrition practices for English Spanish speaking adolescent. Self- Care and Dependent Care Nursing. The Official Journal of International Orem Society 13(1) 9-16. -Munro BH (2005). Statistic Methods in Health Care Research. 5 th edition. Philadelphia, Mosby Co. -Myles J (2007). Management of diabetic foot ulcer. Practice Nurse. 33 (2) 38- 42. -Orem DE (2001) Nursing Conceptsof Practice. 6 th edition. St Louis, A Harcourt HealthSciences Co. -Pashasharifi H (1384). [Psychometric Principles and Mental Trial]. 10 th edition. Tehran, Roshd. (Persian). -Phipps WJ et al (2003). Medical Surgical Nursing: Health & Illness. 6 th edition. USA, Mosby Inc. -Polit DF, Beck TC (2006). Essentials of Nursing Research, Method, Appraisal and Utilization. 6 th edition. Philadelphia, Lippincott Williams and Wilkins. -Reynolds T et al (2000) Assessment of need for elderly. British Journal of Psychiatry. 176(5) 444-452. -Shuldham C et al (2007). Evaluation of European heart failure self-care behavior scale in a united kingdom population . Journal of Advanced Nursing. 60 (1) 87-95. -Slade M et al (2004). Does meeting needs improve quality of life ? Psychotherapy and Psychosomatics. 73(3) 183-189. -Slade M et al (2006). Patient-rated unmet needs and quality of life improvement. The British Journal of Psychiatry. 188(3) 290-295. -Sousa VD et al (2008). Factor analysis of the appraisal of self-care agency scale in American adults with diabetes mellitus. The Diabetes Educator. 34(1) 98-108. -Stuck AE et al (1995) A trial of annual in-home comprehensive geriatric assessment for elderly people living in the community. New England Journal of Medicine. 333(18) 184-189. -Waller Amy et al .Validity, reliability and clinical feasibility of a need assessment tool for people with progressive cancer'. Psycho-Oncology, September 23 2009. [Online]. http://onlinelibrary.wiley.com/doi/10.1002/pon.1624 -Walters K et al (2000). Assessing need from patient, carer and professional perspectives: The Camberwell assessment of need for elderly people in primary care. Age and Ageing. 29(6)05-510. -Weinger K et al (2005). Measuring diabetes self-care. A psychometric analysis of the Self-Care Inventory-revised with adults. Diabetes Care. 28(6)1346-1352. -Yaghmaei F (2007). [Measuring Behavior in Research by Valid & Reliable Instruments.] Tehran: ShahidBeheshti Medical Sciences University Press. (Persian). -Yaghmaei F, Yaghmaei P (1380). [Development an Iranian Instrument to measure attitude to computer]. 1(2) 31-3. (Persian).